Análise dos resultados da implantação da ferramenta de pregão eletrônico nas contratações da administração pública: o caso do IFRJ - Silveira, Flavio de Amorim (2012)
This research considered as a case study the federal autarchy called the Federal Institute of Education, Science and Technology of Rio de Janeiro (IFRJ), traditional school, with over 60 years of service to the state of Rio de Janeiro. Initially presents the historical development of the bidding processes in the world and notably in Brazil, focusing on public administration and an emphasis on Federal Public Administration. This investigation was aimed at identifying and analyzing the results of the implantation of the tool called Electronic Bidding in the Federal Autarchy IFRJ. The tool Electronic bidding embryo whose date of 1997 only had systemic use in the federal public administration after its regulations in 2005 and from there comes the period of analysis. Therefore, this study can be classified as a "single case study" of a qualitative nature. We performed a theoretical analysis that allowed us to understand the progress and evolution of tools bidding that made possible by information technology deployment of this new tool that is still struggling to overcome bureaucratic exacerbation, historical in Brazil. Document research was performed in order to detect if the bidding procedures are achieving the economic objectives desired by the federal government, describing and analyzing the results of the implementation of electronic trading tool in the hiring of federal public administration. Semi-structured interviews were conducted with the criers of the IFRJ with at least one year of performance in the role, following a questionnaire / script, with the aim of, through the perception of respondents, identify and analyze the performance of key indicators of the autarchy IFRJ after the implantation of the Electronic Bidding tool, with emphasis on the efficiency and transparency, using the technique of content analysis (Bardin, 1977). It was observed that even with problems still to solve, the objective is being achieved and the desire of all respondents is that there is a constant improvement in the biddings in order to increase efficiency and transparency, reducing and (in a bigger goal) avoiding misconduct and possible active and passive corruption.